Analysis And Design of Mobile Applications For Make-Up Artist Services (Halomua) With The Design Thinking Framework - Fajri, Fathorazi Nur; Rizal, Fathur; Yaqin, Moh. Ainol; Purwanto, Zendi Ari (Politeknik Ganesha Medan, 2023)
Designing an application user interface design is an important part of creating an attractive application. However, there are several problems such as lack of attention to detail, failure to identify and solve customer problems, and poor planning or organization. The design thinking method performs stages ranging from empathize, define, ideate, and prototype, to usability testing to reduce these problems. At the empathize stage, data is obtained through interviews with MUAs and online questionnaires that have been filled out by respondents. At the define stage, a profile picture of each respondent along with their problems and goals was created. At the idea stage, feature mapping, information architecture, low fidelity wireframe, medium fidelity wireframe, and user flow are made so that it can facilitate users in operating the tasks designed in the application. The prototype stage is to create a flowchart design for each case so that users can find out how the application can run properly. The results of usability and user satisfaction are measured using the System Usability Scale (SUS). The SUS average value of 85.2 is obtained, which means that the value of the UI design results is included in category B with an